1999
DOI: 10.1093/molehr/5.5.487
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of endothelial nitric oxide synthase (eNOS) in human placenta

Abstract: We have investigated the expression and localization of endothelium-derived nitric oxide synthase (eNOS) and the effect of eNOS on placental human chorionic gonadotrophin (HCG) release. eNOS mRNA was found to be expressed in all tissues, with its expression significantly (P < 0.05) increased across gestation. Compared to normal term gestation, placentae from term pregnancies with fetal retardation, or maternal diabetes, but not with maternal hypertension, displayed significantly more (P < 0.05) eNOS mRNA. By i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…This enables the production of higher levels of the vasodilator nitric oxide (NO). This hypothesis is further supported by the finding that placental eNOS expression in elevated in diabetes [24]. GDM is associated with an altered response to vasorelaxing agents [25,26] of feto-placental and umbilical vessels, which furthermore supports the finding of changes in vascular tone.…”
Section: Maternal Gestational Diabetes (Gdm)supporting
confidence: 58%
“…This enables the production of higher levels of the vasodilator nitric oxide (NO). This hypothesis is further supported by the finding that placental eNOS expression in elevated in diabetes [24]. GDM is associated with an altered response to vasorelaxing agents [25,26] of feto-placental and umbilical vessels, which furthermore supports the finding of changes in vascular tone.…”
Section: Maternal Gestational Diabetes (Gdm)supporting
confidence: 58%
“…Indeed, it was recently shown that the eNOS promoter contains a hypoxia response element and thus might be a HIF target gene (11). Expression of iNOS and eNOS has been observed in human and murine placenta (10,41,45). Thus hypoxic upregulation of placental NOS expression may result in NO-mediated vasodilation, thereby increasing placental blood flow and reconstituting oxygen supply to the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured cells were trypsinized and washed twice in phosphate-buffered saline (PBS; Dulbecco), and total RNA was extracted by a single-step method with a Qiagen RNeasy Total RNA extraction reagent set (Qiagen), according to the manufacturer's instructions. measurement of ecNOS mRNA ecNOS mRNA concentrations were analyzed by reverse transcription-PCR (RT-PCR), as described previously, with minor modifications (19 ). Briefly, 1 g of total RNA was reverse-transcribed for 1 h at 37°C in a 20-L volume with use of oligo(dT) primer.…”
Section: Rna Isolationmentioning
confidence: 99%